A cross-domain comparison of application areas for service systems based on cyber-physical systems - Oks, Sascha Julian (8th Service Operations Management Forum, 2015)
Information technology has had a distinct influence on societies, their organizations and industries as well as the lives of their members. The automation of production processes and the usage of personal computers and mobile devices in both work and private related contexts are just a few examples. Nowadays, a further advancement brings inestimable potential based on IT infrastructure: The internet of things. Based on sensors, actuators and data analyzing solutions, cyber-physical systems build the infrastructure for new service systems and business models. Especially for service systems, cyber-physical systems offer a wide range of application fields: First there are end user oriented services systems which can benefit from the functionality and capabilities of cyber-physical systems. Well known examples are services in the field of “smart home” and “smart mobility”. Second, the opportunities for public systems are to mention. Due to the implementation of cyber-physical systems public systems can reach a further level of service quality. Furthermore the interconnection, based on cyber-physical architectures, of these systems allows the emergence of “systems of systems” like “smart grids”. Third, industrial in-plant service systems can profit from the utilization of cyber-physical systems: Besides the widely mentioned profits for inter-machinery communication, the “smart factory” also benefits by integrating the personnel more efficient into production processes. The conducted research compares the three before mentioned application areas in regards of “how cyber-physical systems foster the engineering as well as performance of service systems” for the described users. The methodology of a systematic literature review led to an overview of both chances but also challenges which need to be addressed to enable these individual, economic and organizational potential
Keywords: service systems; service systems engineering; cyber-physical systems